Sistem Penyimpanan Berkas Pegawai Dinas Pariwisata Provinsi Sulawesi Tengah Berbasis Web - Agustiawati Agustiawati; Musfira Musfira (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2025)
A web-based employee data storage system is a website used to store employee files/documents electronically/online. The purpose of this study is to create an employee data storage application and make it easier for employees to search for the data. information system. Data collection techniques used are observation, literature studies and libraries. The research method used is description. The programming language uses PHP and MYSQL and is supported by several frameworks such as CSS, bootstrap, javascript. The results of the program test that have been carried out using the black box testing method, all the main functions of the system can run well according to the needs that have been designed. Testing is carried out on every page and feature, starting from the login process, employee data management, employee file management, to the logout process.